2020
DOI: 10.1590/0034-761220200290
|View full text |Cite
|
Sign up to set email alerts
|

Os desafios do financiamento do enfrentamento à COVID-19 no SUS dentro do pacto federativo

Abstract: Resumo O aprimoramento das regras de financiamento do Sistema Único de Saúde (SUS) em estados e municípios é um dos grandes desafios da saúde pública no Brasil. O objetivo deste artigo é contribuir para este amplo debate, analisando a resposta governamental ao desafio de combate à COVID-19, sob o prisma do financiamento público dos serviços de saúde dos governos subnacionais brasileiros. Uma abordagem quali-quantitativa é adotada, mesclando-se análise documental e análise de regressão. Resultados mostram que n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
18

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 29 publications
1
9
0
18
Order By: Relevance
“…Furthermore, the public health capacity in different municipalities varied greatly. A considerable number of Brazilian regions were receiving less funding from the federal government due to political tension with the leadership [76]. As the country struggled with PPE shortages, unprotected frontline health workers visiting rural areas of Brazil might have unintentionally exposed the vulnerable Indigenous populations they intended to care for with the virus [25].…”
Section: Public Health Capacity and Responsementioning
confidence: 99%
“…Furthermore, the public health capacity in different municipalities varied greatly. A considerable number of Brazilian regions were receiving less funding from the federal government due to political tension with the leadership [76]. As the country struggled with PPE shortages, unprotected frontline health workers visiting rural areas of Brazil might have unintentionally exposed the vulnerable Indigenous populations they intended to care for with the virus [25].…”
Section: Public Health Capacity and Responsementioning
confidence: 99%
“…Unfortunately, not all Brazilian cities that have received Warao immigrants are as satisfactorily structured and organized through a strategic and relevant Plan as in Manaus, which should be recognized in the study. Despite numerous difficulties with underfunding of the Unified Health System, since Brazil is experiencing a serious political and economic crisis, with progressive reduction of financial resources for the SUS in recent years [ 34 ], the study revealed major strides in the universal system from the perspective of ethical, humanitarian, and social inclusion and equity for IVWEG.…”
Section: Discussionmentioning
confidence: 99%
“…Modalidade de aplicação dos recursos da unidade orçamentária Fundo Nacional de Saúde, destinados ao enfrentamento da emergência de saúde pública -COVID19 (SUS/2019-2020). Contudo, registrou-se recorrência da postura do MS (responsável pela maior fatia do financiamento SUS) segundo a qual, mesmo frente a uma emergência internacional de saúde pública, restou mantida a cultura de execução atrelada, não somente a finalidade definida no Programa de Trabalho, mas também aos interesses das áreas finalísticas do MS, limitando a autonomia da gestão e da execução dos recursos recepcionados pelos entes subnacionais [16][17][18][19] . Consequentemente, dos R$32,30 bilhões repassados aos entes subnacionais R$11,88 bilhões (36,8%) tiveram sua execução engessada, dentre eles: R$649,83 milhões (Portaria 2516/20) destinados à aquisição de medicamentos de saúde mental; R$454,33 milhões (Portaria 1857/20) para Saúde na Escola; R$2,24 bilhões (75 Portarias) atrelados a objetos de Emendas Parlamentares.…”
Section: Discussionunclassified